A Century of Growth and Improvement - Friedman, Benjamin M. (American Economic Review, 2016)
The fact that actual economic advance over time normally means producing and consuming different things is usually left implicit in modern models of economic growth. By contrast, qualitative change–new goods and services, and better versions of what already existed–is central to Robert Gordon's history of the improvement of American living standards since 1870. A major contribution of his fine-grained account of this experience is to make clear what this improvement has meant, and why it has mattered to ordinary citizens.